THE ROLE OF THE INTERNATIONAL ASSESSMENT SYSTEM IN SPEECH DEVELOPMENT OF PRIMARY CLASS STUDENTS - Xurramova Madina Abdunazar Qizi; Shabbazova D. R. (Journals Park Publishing, 2023)
In this article, while talking about the requirements of the international assessment program and the principles of introduction into the educational system, the important features of the PISA, PIRLS international assessment programs are revealed based on the opinions of foreign scientists and scientific research works.
Keywords: international evaluation programs, PISA, PIRLS, foreign experiences, national center for evaluation of educational quality, professional competence, reading literacy, level of understanding, educational system.